Empowerment of Santri’s Healthy Lifestyle in Salafi and Modern Islamic Boarding School through Knowledge of Probiotic Food and Beverages - Endro Tri Susdarwono; Ashwar Anis; S. Thoriqul Huda (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2023)
This empowerment is related explicitly to empowering the healthy lifestyle of students in Salafi and modern Islamic boarding schools through knowledge about probiotic food and drinks. This empowerment was carried out for one month, from January 2023 to February 2023. The location of this empowerment was Islamic boarding schools, both Salafi and modern, in Pemalang Regency and Tegal Regency. Data collection techniques in this study will be carried out using questionnaires and test instruments in the form of questions related to the problem. Data processing was carried out quantitatively through statistical tests and qualitatively. For quantitative data processing, statistical tests were used: The test applied was hypothesis testing through the chi-square distribution and hypothesis testing using the Kologorov-Smirnov method. This community empowerment includes several steps or activity procedures carried out as follows: Entrance, Diagnosis, Action Planning, Intervention (Action taking), Evaluation (Assessment), Reflection, and Exit. The results of empowering students in both Salafi and modern Islamic boarding schools can make them adopt a healthy lifestyle through probiotic food and drink accompanied by a holistic understanding of probiotics. Henceforth, these students can pass on this empowerment to other students through the application of peer tutors.